A regulatory network involving Rpo, Gac and Rsm for nitrogen-fixing biofilm formation by Pseudomonas stutzeri - Liguo Shang (Nature Portfolio, 2021)
Abstract Biofilm and nitrogen fixation are two competitive strategies used by many plant-associated bacteria; however, the mechanisms underlying the formation of nitrogen-fixing biofilms remain largely unknown. Here, we examined the roles of multiple signalling systems in the regulation of biofilm formation by root-associated diazotrophic P. stutzeri A1501. Physiological analysis, construction of mutant strains and microscale thermophoresis experiments showed that RpoN is a regulatory hub coupling nitrogen fixation and biofilm formation by directly activating the transcription of pslA, a major gene involved in the synthesis of the Psl exopolysaccharide component of the biofilm matrix and nifA, the transcriptional activator of nif gene expression. Genetic complementation studies and determination of the copy number of transcripts by droplet digital PCR confirmed that the regulatory ncRNA RsmZ serves as a signal amplifier to trigger biofilm formation by sequestering the translational repressor protein RsmA away from pslA and sadC mRNAs, the latter of which encodes a diguanylate cyclase that synthesises c-di-GMP. Moreover, RpoS exerts a braking effect on biofilm formation by transcriptionally downregulating RsmZ expression, while RpoS expression is repressed posttranscriptionally by RsmA. These findings provide mechanistic insights into how the Rpo/Gac/Rsm regulatory networks fine-tune nitrogen-fixing biofilm formation in response to the availability of nutrients.